Application of Decoupling Approach to Evaluate Electricity Consumption, Agriculture, GDP, Crude Oil Production, and CO2 Emission Nexus in Support of Economic Instrument in Nigeria - Sane, Mathy; Hajek, Miroslav; Phiri, Joseph; Babangida, Jamilu Said; Nwaogu, Chukwudi (MDPI, 2022)
The paper appraised the nexus between electricity consumption, agriculture, GDP, oil production, and carbon dioxide (CO2) emissions in Nigeria using a decoupling approach. The result showed that agriculture, electricity, and GDP were predictive variables for CO2 emissions in the Granger causality analysis. The relationship between GDP and CO2 emissions also indicated that the amount of CO2 released tends to rise as the economy's output and industrial sectors grow, making GDP and CO2 emissions increasingly relevant indicators as a driver of CO2 emissions. Modern agriculture is reliant on large-scale use of fossil fuels and fertilizer production, as well as GHG emissions from crop and livestock production. However, increasing per capita real production can help to enhance quality of the environment, and speed up the uptake of renewable energy which can consequently help to ameliorate global warming. As a result of this study's policy implications, policies in the agricultural sector that could combat CO2 emissions, including deforestation, land clearing, fertilization with highly environmentally destructive chemicals, neglected integration of agroforestry, and social forestry practices, can help reduce CO2 emissions in the agricultural sector. In addition, the study recommends that the financial markets' monetary policy should regulate the GDP to charges to compensate for their various sectors' contributions to CO2 emissions. This investigation might help policymakers in Nigeria to define the CO2 emission monetary and fiscal strategies. In addition, more alternative energy sources such as biofuels, hydropower, solar energy, and other renewable resources should be embraced in Nigeria as sustainable substitutes for fossil fuels.
Keywords: climate change; renewable energy; non-renewable energy; environmental-economic factors; decoupling method; Nigeria; ENERGY-CONSUMPTION; FINANCIAL DEVELOPMENT; CARBON EMISSION; GROWTH; DECOMPOSITION; TRADE; URBANIZATION; QUALITY; IMPACT; Science & Technology - Other Topics; Environmental Sciences & Ecology